1997
DOI: 10.1079/bjn19970053
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of exercise on energy intake and feeding behaviour

Abstract: The main objective of the present study was to evaluate the short-term effects of exercise of different intensities on energy intake. Eleven young men were submitted to three randomly assigned sessions (one control and two exercise sessions) in which they ate, ad libitum, foods from a buffet-type meal.The energy cost of exercise was the same in the two exercise sessions. Results showed that there was no significant change in post-exercise subjective levels of hunger and fullness as well as total energy and mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
122
1
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(140 citation statements)
references
References 18 publications
12
122
1
5
Order By: Relevance
“…It is perhaps surprising that acylated ghrelin concentrations were not elevated toward the end of the exercise trials, since energy intake was not increased in these trials to compensate for the energy expended during exercise. These data are consistent with the recent finding that postexercise ghrelin responses may be independent of energy balance (22) and lend support to previous research that indicated acute exercise does not increase energy intake in the short term, i.e., 1 to 2 days after exercise (6,7,24,28,29). It would be of interest to examine acylated ghrelin concentrations the day after exercise to assess whether values are elevated in response to a shortterm negative energy balance.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is perhaps surprising that acylated ghrelin concentrations were not elevated toward the end of the exercise trials, since energy intake was not increased in these trials to compensate for the energy expended during exercise. These data are consistent with the recent finding that postexercise ghrelin responses may be independent of energy balance (22) and lend support to previous research that indicated acute exercise does not increase energy intake in the short term, i.e., 1 to 2 days after exercise (6,7,24,28,29). It would be of interest to examine acylated ghrelin concentrations the day after exercise to assess whether values are elevated in response to a shortterm negative energy balance.…”
Section: Discussionsupporting
confidence: 81%
“…Exercise is an effective method of increasing energy expenditure (2), and it may, paradoxically, lead to a short-term hunger suppression (6,7,24,28,29). This relationship between exercise and hunger has led investigators to study the role of gut hormones in mediating exerciseinduced hunger changes.…”
mentioning
confidence: 99%
“…Thompson and colleagues (1988) demonstrated greater appetite suppression during exercise as intensity increased but no difference in energy intake after exercise, whereas Imbeault et al (1997) found no differences in appetite but decreased energy intake as exercise intensity increased. Alternatively, Ueda and colleagues (2009) found no difference in the appetite or energy intake responses to different intensity exercise bouts.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data has shown that exercise has a strong impact on ad libitum energy intake [63][64][65][66][67][68]. For example, King et al showed that 60 minutes of swimming suppressed relative energy intake (energy intake minus energy cost of exercise), compared to a resting condition, in trained men [65].…”
Section: Exercise and Ad Libitum Energy Intakementioning
confidence: 99%